A Qualitative exploration Of A Support Group Intervention Among Women With Cervical Cancer At Tiyanjane Clinic For Palliative Care, Queen Elizabeth Central Hospital, Blantyre, Malawi. - Nkhoma, Mwandida Mdazepa Matilda (Department of Public Health and Family Medicine, 2021)
Background: Cancer of the cervix is a common malignancy among women and is one of the leading causes of cancer morbidity and mortality in Malawi. The majority of women with cervical cancer present with advanced disease where cure is not possible. These women face many challenges that affect their lives holistically. In particular, the psycho-social impact is common for women living with cervical cancer and psychosocial care does not have sufficient attention as the focus is management of the disease and physical symptoms. However, research shows that support groups are associated with improvements in intimacy, emotional support and becoming better informed for women living with cancer of the cervix. Methodology: This was a qualitative research study. Semi structured interviews were used to collect data and were audio-taped. A purposive sampling technique was used in selection of participants. One to one interviews were conducted with eight (8) women diagnosed with cervical cancer because data saturation was reached at that number. Thematic analysis was undertaken where four phases of organisation, familiarization, reduction and analysis were used. Results: The following themes were identified: intimacy, emotional support, becoming informed and drawbacks of support group. Conclusion: A support group intervention is found to reduce psychosocial and intimacy distress associated with cervical cancer diagnosis. This leads to improved quality of life of these women and their families. Thus, a support group intervention has a potential to enhance appropriate holistic management plans for women with cervical cancer.